Xavier Tubau, Erasmo mediador: política y religión en los primeros años de la Reforma, Valladolid, Universidad de Valladolid, 2012, 138 pp. ISBN 978-84-8448-724-1 (Minerva, 2019)
Review: Xavier Tubau, Erasmo mediador: política y religión en los primeros años de la Reforma, Valladolid, Universidad de Valladolid, 2012, 138 pp. ISBN 978-84-8448-724-1